2018
DOI: 10.1149/08605.0111ecst
|View full text |Cite
|
Sign up to set email alerts
|

Glass Frit Wafer Bonding for Encapsulating Monolithic Integrated CMOS-MEMS Devices

Abstract: CMOS-MEMS integration is getting a more and more important topic with growing expectations and requirements on the function and performance of micro sensors [1]. The integration of ASICs and memories to MEMS sensor structures allows by calibration the compensation of side effects (temperature influences, stress influences,…) and manufacturing tolerances. Thus, very accurate sensors, at acceptable cost structures for high volume applications become feasible. These high volume applications are often for mobile d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In parallel, conductive tracks or metallic lead-throughs for device signaling can be covered within the softened glass, preventing the need for processing complex and obviously more expensive vertical device signaling [ 48 , 49 ], with new questions arising related to hermeticity and device design and compatibility. Additionally, glass-frit bonding offers process flexibility due to a wide variety of suitable substrates including CMOS compatibility [ 50 ]. By application-related benchmarking of glass-frit bonding with alternative WLVP, glass-frit bonding can offer a good compromise of challenges, advantages, and disadvantages with respect to the specific features of the final application [ 39 ], required tooling, and the involved manufacturing processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In parallel, conductive tracks or metallic lead-throughs for device signaling can be covered within the softened glass, preventing the need for processing complex and obviously more expensive vertical device signaling [ 48 , 49 ], with new questions arising related to hermeticity and device design and compatibility. Additionally, glass-frit bonding offers process flexibility due to a wide variety of suitable substrates including CMOS compatibility [ 50 ]. By application-related benchmarking of glass-frit bonding with alternative WLVP, glass-frit bonding can offer a good compromise of challenges, advantages, and disadvantages with respect to the specific features of the final application [ 39 ], required tooling, and the involved manufacturing processes.…”
Section: Discussionmentioning
confidence: 99%
“…For this work, glass-frit bonding [ 47 , 48 , 49 , 50 , 51 , 52 ] is the most reliable bonding method, allowing hermetic sealing over surface topologies several µm high. This bonding approach allows realizing hermetic electrical interconnects using existing metal lines without complex technological changes for the DW.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hermeticity is a big benefit of the glass frit bonding, and therefore was intensively investigated. In these investigations 12,13 it was found that hermeticity issues often occur at the wafer edge, not all around, but typically at the left and and/or right side of wafers as shown in Fig. 17.…”
Section: Wafer Edge Aspects At Wafer Cap Wafer Bondingmentioning
confidence: 97%